Clinical value of dynamic testing of viral load level in blood at patients with natural course of chronic HBV-monoinfection - S. A. Shutko; K. R. Dudina; O. O. Znoyko; Ye. A. Klimova; V. I. Kashirin; D. S. Cheshik; N. D. Yushchuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Aim of investigation. To determine clinical value of viral load level (VLL) of HBV in blood at patients with natural course of chronic HBV-monoinfection.Material and methods. Overall 149 patients were investigated. Of them 68 (45,6%) were women and 81 man (54,4%) in the age of 16 to 71 years. Molecularbiological analysis for the presence of hepatitis B virus DNA in blood was carried out three times with 6 months intervals by polymerase chain reaction (PCR) method in a «real time» mode (test-sensitivity 103 copies/ml).Results. At triple complex investigation 20% of HBsAg inactive carriers have been selected. At a single PCR – test at the majority (59,5%) of patients with chronic hepatitis B (CHB) no HBV DNA was determined in a blood, while at two-times and triple study the number of patients with not determined HBV DNA level reduced apparently (41 and 12,5% respectively). Analysis has indicated, that CHB patients have direct correlation between alanine transaminases (ALT) activity and HBV DNA VLL (r=0,385, р=0,008). Only in 9% of cases constantly high VLL was registered, mainly, on a background of elevated activity of ALT. The progressing form of CHB has been diagnosed in 21,7% of patients with natural course of chronic HBV-monoinfection for this they have been recognized as candidates for antiviral therapy.Conclusions. In original study the direct correlation between parameters of HBV VLL and ALT activity at patients with natural course of chronic HBV-monoinfection was revealed. Only complex dynamic assessment of such patients helps to define absolute candidates for prescription of antiviral therapy and to determine proportion of inactive HBsAg carriers.